2017
DOI: 10.1002/etc.3781
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated phenolic compounds in wild fish from Canadian Areas of Concern

Abstract: Concentrations of halogenated phenolic compounds were measured in the plasma of brown bullhead (Ameiurus nebulosus) from 4 Canadian Areas of Concern (AOCs), to assess exposure to suspected thyroid‐disrupting chemicals. Hydroxylated polychlorinated biphenyls (OH‐PCBs) were detected in every sample collected in 3 of the AOCs; the detection frequency was lower in samples from the Detroit River AOC. The OH‐PCBs most frequently detected were pentachloro, hexachloro, and heptachloro congeners, which are structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…A toxicokinetics study by Buckman et al [191] also suggested that fish may accumulate a significant amount of OH-PCB metabolites from sources other than biotransformation from parent PCB congeners and/or are produced over a longer period of time than assessed in the study at low temperatures. Hydroxylated PCBs have been studied and reported in humans [127][128][129][192][193][194][195][196] and different environmental matrices such as biota [197][198][199][200][201][202][203][204][205][206][207], sediments [131], sludges [132], air [133][134], water and precipitation [125].…”
Section: Some Of the Formation Pathways Of Oh-pcbs Include The Oxidat...mentioning
confidence: 99%
“…A toxicokinetics study by Buckman et al [191] also suggested that fish may accumulate a significant amount of OH-PCB metabolites from sources other than biotransformation from parent PCB congeners and/or are produced over a longer period of time than assessed in the study at low temperatures. Hydroxylated PCBs have been studied and reported in humans [127][128][129][192][193][194][195][196] and different environmental matrices such as biota [197][198][199][200][201][202][203][204][205][206][207], sediments [131], sludges [132], air [133][134], water and precipitation [125].…”
Section: Some Of the Formation Pathways Of Oh-pcbs Include The Oxidat...mentioning
confidence: 99%